Bernard Williams and the concept of shame: What makes an emotion moral? - Mendonça, Dina; Cadilha, Susana (Labyrinth, 2019)
The paper proposes a way to understand moral emotions in ethics building upon Bernard Williams' claim that feelings, emotions and sentiments are an integral part of rationality. Based upon Bernard Williams' analysis of shame we argue that the richness and thickness that it is attached to some emotions is the key to understand why some emotions have a distinct ethical resonance. The first part takes up Bernard Williams' philosophical assessment of the concept of shame (Williams 1993) establishing a general framework to show how recent developments in philosophy of emotions are in line with the far-reaching consequences of Bernard Williams' insights. Then we highlight the way in which there is both an historical relativity to emotions and an intemporal understanding of their ethical role, and use the concept of meta-emotion to reinforce the idea that what makes some emotions moral requires employing Williams' distinction between thick and thin concepts.